Multidisciplinary analysis of the transient performance of a 20 kW class HTS induction/synchronous motor cooled with a cryocooler and gaseous air-gap coolant. (April 2019) - Karashima, T.; Nakamura, T.; Okuno, M.
Highlights: High temperature superconducting induction/synchronous motor. Multidisciplinary analysis of motor characteristics. Cooling by means of a cryocooler and gaseous air-gap coolant. Transient characteristics analysis. Abstract: This paper presents a multidisciplinary analysis procedure for the transient cooling and rotating characteristics of a 20 kW class high temperature superconducting (HTS) induction/synchronous motor, this analysis couples the nonlinear voltage equations, equation of motion, and a thermal equivalent circuit. First, the quantitative accuracy of the thermal equivalent circuit is validated through comparison with results obtained using the 3D finite element analysis. Then, multidisciplinary analysis is performed with the assumption that the outer surface of the stator is cooled by a cryocooler and the air-gap between the stator and rotor is cooled by a gaseous coolant. It is demonstrated that the transient performance of the motor can be fully determined using our developed procedure. For instance, we can determine the gas-flow speed in the air-gap required for cooling of the HTS rotor, by assuming appropriate expressions for the heat transfer in the air-gap. The analysis procedure and obtained results are effective for investigation of the variable speed performance of an HTS motor system and for optimal design of the motor cooling structure and method.